LEGAL PROTECTION FOR LOCAL PRODUCTS IN ASEAN MARKET LIBERALISM: A Legal Analysis and Fiqh Muamalah Perspective - Rozatul Fadilla Azza; Chairul Fahmi; Riza Afrian Mustaqim (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Market liberalisation in Southeast Asia through the ASEAN Economic Community (AEC) has created a new economic paradigm that emphasises the free flow of goods, services, and investment. However, this integration poses significant challenges to the sustainability of local products, especially those produced by Micro, Small, and Medium Enterprises (MSMEs). This journal aims to analyse in depth the legal protection mechanisms for local products in Indonesia within the framework of ASEAN liberalism and review them from the perspective of Fiqh Muamalah. Using a normative juridical approach, this study examines the synchronisation of Indonesian positive law, such as the Trade Law and the Job Creation Law, with sharia principles such as justice (‘adl), benefit (maslahah), and protection (himayah). The analysis shows that although national legal instruments have sought to protect through non-tariff measures and the empowerment of MSMEs, structural imbalances and regulatory ambiguities continue to harm local producers. The Fiqh Muamalah perspective offers a reconstruction of policy through the state’s role as murabbī (guide) to ensure market balance and economic sovereignty for the people.